Electric field modulation of energy transfer along intermediate filaments isolated from porcine retina - Khmelinskii, Igor (2020)
We report an experimental method for simultaneous measurement of the electric properties and energy transfer by natural biological fibers. We found that energy transfer efficiency along intermediate filaments (IFs) isolated from porcine retina varied with the potential difference applied to these IFs. The maximum measured effect amounted to 25% of the transfer efficiency increase. The recorded I/U plots characteristic of the IFs demonstrate the behavior of a semiconductor with 0.62 eV band gap. These results show that the image signal might be modulated by the potential difference across the cell membrane, facilitating image contrast enhancement in the brain.